Answer:
The answer is 61.35 s
Step-by-step explanation:
We start by writing the distance equations:
d = xtug + xasteroid (eq. 1)
xtug = votug*t + (atug*t^2)/2; if votug = 0, we have:
xtug = (atug*t^2)/2
xasteroid = voasteroid*t +(aasteroid*t^2)/2; if voasteroid = 0, we have:
xasteroid = (aasteroid*t^2)/2
replacing in equation 1:
d = (atug*t^2)/2 + (aasteroid*t^2)/2 = (atug + aasteroid)*t^2/2
Clearing t:
t = ((2*d)/(atug + aasteroid))^1/2
applying Newton's second law we have:
F = m*a; F = force, m = mass, a=acceleration
a= F/m
t = ((2*d)/(F*((1/mtug) +(1/masteroid))))^1/2 = ((2*432)/(518*((1/3740) + (1/5690))))^1/2 = 61.35 s